Sludge and oil refining of non-ferrous metallurgy waste in the production of building materials use - Tolepbergen, Сандуғаш (Рroblems of engineering and professional education, 2023)
In this paper, described the possibility of using oil sludge and non-ferrous metallurgy waste in the production of building materials that occupy vast territories and are dangerous pollutants of the environment of Kazakhstan. Methods for the production of porous ceramic building material by the method of chemical pore formation are given.